Margin Requirements, Speculative Trading, and Stock Price Fluctuations: The Case of Japan - Hardouvelis, G. A.; Peristiani, S. (Quarterly Journal of Economics, 1992)
An increase in margin requirements in the First Section of the Tokyo Stock Exchange is followed by a decline in margin borrowing, trading volume, the proportion of trading performed through margin accounts, the growth in stock prices, and the conditional volatility of daily returns. The nonmarginable Second Section stocks show a smaller change in volatility and only a delayed weak price response. The hypothesis that margin requirements restrict the behavior of destabilizing speculators can explain these correlations but cannot explain the observation that individuals, the most active users of margin funds, appear to be good market timers.